Badlands as a hot spot of petrogenic contribution to riverine particulate organic carbon to the Gulf of Lion (NW Mediterranean Sea). Issue 12 (25th May 2018) - Copard, Yoann; Eyrolle, Frédérique; Radakovitch, Olivier; Poirel, Alain; Raimbault, Patrick; Gairoard, Stéphanie; Di‐Giovanni, Christian
Abstract: Determining the riverine carbon fluxes to oceans is critical for an improved understanding of C budgets and biogeochemical cycles (C, O) over a broad range of spatial and time scales. Among the particulate organic carbon (POC) involved in these fluxes, those yielded by sedimentary rocks (petrogenic POC: pPOC) remain somewhat uncertain as to their source on continental surfaces. Based on time series from long‐term observatories, we refine the POC and sediments flux of the Rhône River, one of the major tributaries to the Mediterranean Sea. Radiocarbon measurements on a set of riverine samples and forward modelling were used to (i) determine a modelled pPOC content and pPOC/POC ratio for each sample set, (ii) assess pPOC flux delivered to the NW Mediterranean Sea, and (iii) estimate the badlands contribution from the Durance catchment to both the pPOC and to sediment discharges. The weighted pPOC flux contributes up to 26% of the POC flux (145 Gg yr ‐1 ) discharged into the Mediterranean Sea, whereas the weighted pPOC content reaches 0.31 wt%. Despite their low contributive surface area (0.2%), badlands provide, respectively, 12, 3.5 and 14% of the pPOC, POC and sediment fluxes to the Rhône River. Consequently, such rocks can be considered as a major source of pPOC and sediments for the NW Mediterranean Sea and potentially for oceans. We suggest that river‐dominated ocean margins, such as the Rhône River, with badlands in their catchment could export a significant amount of pPOC to the oceans. Copyright © 2018 John Wiley & Sons, Ltd. Abstract : We refine the particulate organic carbon (POC) and sediments flux of the Rhône River. Using 14 C data and forward modelling, a quarter of this POC has a petrogenic origin. Despite their small surface areas, marly badlands outcropping in the Durance catchment are viewed as a significant continental source of petrogenic POC and sediments. We suggest that river‐dominated ocean margins, such as the Rhône River, with badlands in their catchment could export large amounts of pPOC to marine environments.